Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1159/000112073
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the highly repeated fraction of the banana genome

Abstract: Although the nuclear genome of banana (Musa spp.) is relatively small (1C ∼ 610 Mbp for M. acuminata), the results obtained from other sequenced genomes suggest that more than half of the banana genome may be composed of repetitive and non-coding DNA sequences. Knowledge of repetitive DNA can facilitate mapping of important traits, phylogenetic studies, BAC-based physical mapping, and genome sequencing/annotation. However, only a few repetitive DNA sequences have been characterized in banana. In this work, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 75 publications
1
28
0
1
Order By: Relevance
“…At the same time, breeding of improved cultivars is hampered by seed sterility, unknown origin of the cultivated clones, and poor knowledge on genetic diversity of the genus Musa . The nuclear genome of Musa species is relatively small (1C∼600 Mbp; [16], [17]), and previous studies showed that ∼55% of the genome is represented by repetitive DNA, especially different types of retroelements [18][20]. Genomic repeats evolve more rapidly than coding sequences, and plant geneticists and breeders found them a unique source of molecular markers to map important genes, analyze genetic diversity, and study processes of speciation and genome evolution [21][23].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, breeding of improved cultivars is hampered by seed sterility, unknown origin of the cultivated clones, and poor knowledge on genetic diversity of the genus Musa . The nuclear genome of Musa species is relatively small (1C∼600 Mbp; [16], [17]), and previous studies showed that ∼55% of the genome is represented by repetitive DNA, especially different types of retroelements [18][20]. Genomic repeats evolve more rapidly than coding sequences, and plant geneticists and breeders found them a unique source of molecular markers to map important genes, analyze genetic diversity, and study processes of speciation and genome evolution [21][23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that about 55% of the genome is made of various DNA repeats [5], but only a limited number of repetitive DNA sequences has been characterized. Valárik et al .…”
Section: Introductionmentioning
confidence: 99%
“…(Katsiotis et al, 1997), banana (Musa spp. ;H ribová et al, 2007), and other plant species (Sharma and Raina, 2005) because they tend to form clusters, which facilitates their detection and positive chromosome identification. In this study, 11 newly characterized satellites provided localized signals on one or more chromosomes of meadow fescue and could serve as new cytogenetic markers in this species and probably also in ryegrasses.…”
Section: Newly Identified Repeats Are a Valuable Source Of Cytogenetimentioning
confidence: 99%